2015
DOI: 10.1007/s40121-015-0096-4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Methicillin-Resistant Staphylococcus aureus (MRSA) Pneumonia with Ceftaroline Fosamil in a Patient with Inhalational Thermal Injury

Abstract: A 48-year-old female, who was found unresponsive and suffered inhalation injury secondary to a house fire, was transferred to our burn center for definitive treatment. Post tracheostomy, the patient became febrile and tachycardic. On hospital day (HD) 5, the patient expressed thick yellow secretions during suctioning and diffuse rhonchi was noted on physical exam. Blood cultures and a culture from the broncheo-alvelolar lavage grew Gram-positive cocci in clusters and the patient was started on empiric vancomyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
(34 reference statements)
0
5
0
1
Order By: Relevance
“…Other agents for the treatment of CA-MRSA are under evaluation, and ceftaroline, although not approved for MRSA pneumonia, has been reported to show efficacy in treating MRSA pneumonia and bacteremia unresponsive to vancomycin. 43…”
Section: Community-associated Methicillin-resistant Staphylococcus Aumentioning
confidence: 99%
“…Other agents for the treatment of CA-MRSA are under evaluation, and ceftaroline, although not approved for MRSA pneumonia, has been reported to show efficacy in treating MRSA pneumonia and bacteremia unresponsive to vancomycin. 43…”
Section: Community-associated Methicillin-resistant Staphylococcus Aumentioning
confidence: 99%
“…As of 10 January 2023, there were 541 results for the search "ceftaroline AND MRSA" and 195 results for the search "ceftaroline AND MRSA AND pneumonia". In total, 14 publications were identified for data extraction and inclusion in the qualitative analysis, ranging in publication date from 2012 to 2021 [53][54][55][56][57][58][59][60][61][62][63][64][65][66] publications reported the use of ceftaroline fosamil doses and/or duration of treatment that do not reflect current approved labelling. Across the 14 included publications, a total of 1908 patients were treated with ceftaroline fosamil and 264 patients were reported to have MRSA pneumonia or MRSA isolated from a lower respiratory tract source.…”
Section: Search Resultsmentioning
confidence: 99%
“…Across three studies that reported outcomes for 44 patients with unspecified MRSA pneumonia treated with ceftaroline fosamil, clinical success rates were 50–80%; 85–100% of patients in these studies had received prior antimicrobial therapy for MRSA [ 55 , 62 , 63 ]. In two individual case studies of patients with MRSA HAP or VAP, clinical success rates were zero out of one (0%) and one out of one (100%), respectively; in both of these cases, ceftaroline fosamil was given as second-line treatment following inadequate responses to other anti-MRSA treatments [ 56 , 61 ]. The case which reported clinical failure (MRSA pneumonia in a 65-year-old female admitted to the ICU) was also associated with eosinophilic pneumonia which was attributed to ceftaroline fosamil and subsequently resolved with additional medical treatment [ 61 ].…”
Section: Literature Searchmentioning
confidence: 99%
“…Bu sonuçlarla birlikte seftarolinin onay aldığı CYDİ ve TK-Pnömoni dışındaki endikasyonlarda başarı ile kullanılabileceğini gösteren benzeri in vitro ve in vivo çalışmalar da bulunmaktadır (12,16,18,24,30) .…”
Section: çAlışmaunclassified